Exploring Sensitive Nursing Issues Through Focus Group Approaches - Andreou, Panayiota; Papastavrou, Evridiki (My University, 2012)
Background: Rationing of nursing care is an important organisational variable that includes omissions in care and appears to be related to patient safety and quality of care. Nursing care rationing is a sensitive issue that raises strong emotions as nurses are not always willing to report omitted or unfinished nursing tasks. Apart from the negative consequences for patients, rationing may add an ethical burden on nurses causing moral distress. Aim: The aim of this paper was to explore some of the methodological issues arising from using focus group interviews as a research method when investigating “sensitive nursing issues”, in this case rationing of nursing care. Material and Method: Methodological issues are discussed in the context of a study examining views of nursing care rationing among registered nurses working in medical and surgical units. Three focus groups were held, between June and September 2011, to identify which areas of nursing care are rationed and the underlying causes of rationing. The groups comprised of a total of seventeen registered nurses. The discussion started based on a scenario describing a regular day in a busy hospital ward and the purpose was to use group dynamics and participant interaction to gain an in-depth discussion of the participants’ views. Results: The security provided by the focus group encouraged the exploration of less conventional positions and facilitated conversation about sensitive events like the admission of rationing nursing care tasks. The group participation has given the nurses the opportunity to listen to colleagues having similar experiences and created an atmosphere of openness and honesty. Conclusions: Focus-group interviews as a data collection strategy for sensitive nursing issues is a rich source of information.
Keywords: Focus groups; Nursing; Nurses; Nursing care